The performance analysis of screw pump stator elastomers: Polyamide 6/hydrogenated nitrile blends: Mechanical, oil resistance and tribological properties - Yufang Li; Danli Nie; Ziqing Cai (Polymer Testing, 2023)
In this paper, the mechanical properties, thermal properties, oil resistance and tribology performance of hydrogenated nitrile/polyamide 6 blends were studied systematically. The inter-molecular interaction, phase separation structure, crystallinity, dynamic loss, friction morphology and other aspects of the blends were investigated. The results showed that PA6 phase had significant reinforcing effect in HNBR matrix. Due to the strong interaction between PA6 molecular chain and HNBR molecular chain, the glass transition temperature (Tg) of the blends was increased and the dynamic loss factor (tanδ) was decreased. Meanwhile, the tribology performance of the blends was significantly improved. It was due to the formation of a microball layer with PA6 particle phase as component, which effectively isolated the contact between the friction pairs.